Arthroscopic Superior Capsular Reconstruction for Older Patients With Irreparable Rotator Cuff Tears: A Comparative Study With Younger Patients. Issue 10 (August 2021) - Kholinne, Erica; Kwak, Jae-Man; Cho, Chang-Ho; AlSomali, Khalid; Van Nguyen, Thanh; Kim, Hyojune; Koh, Kyoung-Hwan; Jeon, In-Ho
Background: Arthroscopic superior capsular reconstruction (ASCR) is a method for treating irreparable chronic rotator cuff tears. However, the extent to which ASCR can be performed with regard to the patient's age has yet to be determined. Purpose: To compare the surgical outcomes of ASCR for the treatment of irreparable rotator cuff tears (IRCTs) in patients aged <65 years versus patients aged ≥65 years. Study Design: Cohort study; Level of evidence, 3. Methods: Of 105 patients with IRCTs who underwent ASCR between March 2013 and June 2020, 73 patients were enrolled in this study based on the selection criteria. Polypropylene mesh augmentation to the graft was used in 18 of 36 patients in the younger adults group (age, <65 years) and 20 of 37 patients in the older adults group (age, ≥65 years). The clinical and radiological outcomes were evaluated preoperatively and at the final clinical follow-up. The graft integrity status was evaluated using serial magnetic resonance imaging and set as the primary endpoint. Furthermore, subgroup analysis was performed based on age group and graft type. Results: The mean age of the patients was 59.2 ± 3.8 years in the younger adults group and 70.5 ± 4.1 years in the older adults group. Both groups showed improvement based on the clinical and radiological outcomes at the final follow-up. The mean American Shoulder and Elbow Surgeons scores improved from 52.3 ± 15.4 to 77.3 ± 13.5 in the younger adults group ( P < .001) and from 45.7 ± 16.1 to 76.6 ± 11.4 in the older adults group ( P < .001). The mean visual analog scale for pain scores improved from 5.5 ± 1.2 to 2.1 ± 0.9 in the younger adults group ( P < .001) and from 5.5 ± 1.4 to 2.1 ± 1.2 in the older adults group ( P < .001). The graft healing rate was significantly higher in the younger adults group (81%) than in the older adults group (65%) ( P = .049). Subgroup analysis showed that after mesh augmentation, the healing rate in the younger adults group (84%) was similar to that in the older adults group (85%) ( P = .299). Conclusion: ASCR resulted in a favorable surgical outcome for both younger and older adult patients with IRCT. The younger patients had lower graft failure rates and superior surgical outcomes. In older patients, ASCR using polypropylene mesh augmentation may reduce graft failure and result in surgical outcomes similar to those in younger patients.